2017
DOI: 10.1002/joc.5023
|View full text |Cite
|
Sign up to set email alerts
|

Employing an urban meteorological network to monitor air temperature conditions in the ‘local climate zones’ of Szeged, Hungary

Abstract: We analyse the average annual and seasonal air temperature conditions in the ‘local climate zones’ (LCZs) of Szeged, Hungary. The basis of our analysis is a 1‐year dataset from 2014 to 2015 for a 20‐station urban meteorological network. The network and its corresponding LCZ classes put temperature studies in Szeged into a new spatial framework to assess local climate and urban heat island (UHI) conditions. The stations were installed at locally representative sites using a Geographic Information System (GIS) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
92
0
24

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(129 citation statements)
references
References 33 publications
13
92
0
24
Order By: Relevance
“…A similar distribution across LCZs is observed for EAFT and LAFT, except that T2M is approximately 1 K higher during the LAFT for all the LCZs. At NIGHT, both the inter and intra‐LCZ T2M ranges increase, which is consistent with previous findings on more prominent UHIs and larger intra‐LCZ variabilities in cities at night (Alexander and Mills, ; Stewart et al, ; Leconte et al, ; Fenner et al, ; Skarbit et al, ). Generally, the T2M is higher for LCZ 1/2/3, LCZ 4/5, LCZ 6, and LCZ 8 (hereafter “built LCZs”) than for LCZ A, LCZ B, LCZ D, and LCZ G (hereafter “natural LCZs”).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…A similar distribution across LCZs is observed for EAFT and LAFT, except that T2M is approximately 1 K higher during the LAFT for all the LCZs. At NIGHT, both the inter and intra‐LCZ T2M ranges increase, which is consistent with previous findings on more prominent UHIs and larger intra‐LCZ variabilities in cities at night (Alexander and Mills, ; Stewart et al, ; Leconte et al, ; Fenner et al, ; Skarbit et al, ). Generally, the T2M is higher for LCZ 1/2/3, LCZ 4/5, LCZ 6, and LCZ 8 (hereafter “built LCZs”) than for LCZ A, LCZ B, LCZ D, and LCZ G (hereafter “natural LCZs”).…”
Section: Resultsmentioning
confidence: 95%
“…Large intra‐LCZ variabilities are found for LCZ 6 and LCZ 8, which may be due to the heterogeneity in urban form owing to their locations at urban–rural boundaries, or simply as a result of the large number of data points (Figure ). Interestingly, the large intra‐LCZ variability for LCZ 6 is also observed in Berlin (Germany; Fenner et al, ) and Szeged (Hungary; Skarbit et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perini and Magliocco [24] testified that higher density caused higher air temperature in Italy. A study conducted in Szeged, Hungary found that densely built-up areas had higher annual and monthly mean and minimum air temperatures than structurally open and more vegetated areas [35]. However, in an experimental study conducted in Hong Kong (a typical compact city), it was found that sites with higher density experienced lower air temperature [36].…”
Section: Land Use Intensity Descriptorsmentioning
confidence: 97%